12. Outcome prediction in comatose patients after cardiac arrest, the utility of early EEG/SEP recordings during therapeutic hypothermia: The italian multicentric study (PRONECA) preliminary data. Issue 12 (December 2016) - Grippo, A.; Carrai, R.; Audenino, D.; Callegarin, C.; di Capua, M.; Lombardi, M.; Mecarelli, O.; Minardi, C.; Minicucci, F.; Motti, L.; Politini, L.; Valzania, F.; et al.
Abstract : Somatosensory evoked potentials(SEPs) and EEG are reliable outcome predictors of coma after cardiac arrest (CA). Nevertheless, only few multicentric studies are available. Aim of the study was to evaluate the prognostic value of EEG and SEPs association in post-anoxic comatose patients at different recording time from cardiac arrest (CA) in an Italian multicentric study. Comatose patients after CA treated with TH were included. EEG and SEPs were recorded within 12 h and at 72 h after CA. EEG was classified into "non-continuous" and "continuous". SEPs were dichotomized into "bilaterally absent" (BA) and "present". Neurologic outcome was evaluated at 6 months by GOS: "awakening"(GOS 3–5) was considered good outcome. 83 patients were included to date. "Continuous" EEG pattern at 12 h always predicted good outcome, "non-continuous" pattern at 72 h always predicted poor outcome. BA SEPs always predicted poor outcome. Early "continuous" EEG pattern was always associated with present SEPs. SEPs provide a specific and time-independent predictor of poor outcome. EEG provide a specific and time-dependent predictor of good outcome (at <12 h) and poor outcome (at 72 h). Early "continuous" EEG and BA SEPs are never associated together. Combined EEG/SEPs recordings are a useful tool for reliable prognostication both of good and poor outcome in comatose patients treated with TH.